Pengaruh Overconfidence, Gambler’s Fallacy dan Loss Aversion Terhadap Keputusan Investasi di Sumatera Utara - Fauziah Rahman; Sucitra Dewi (Jurnal Riset Akuntansi dan Bisnis, 2023)
This study aims to prove the effect of overconfidence, loss aversion, gambler's fallacy, on investment decisions. The type of research used is conclusive causality which aims to see the cause-and-effect between the dependent variable and the independent variable. This research study uses primary data obtained from distributing questionnaires through social media. The population in this study were all capital market investors in North Sumatra. Due to the unknown population, the sampling used Malhotra's theory with purposive sampling technique so that 190 samples were obtained in this study. The results stated that overconfidence, loss aversion and gambler's fallacy partially had a positive and significant effect on investment decision making. Other results overconfidence, loss aversion and gambler's fallacy simultaneously have a positive and significant effect on investment decision making